Introduction: Parties and Voters at the 2013 German Federal Election. Issue 1 (2nd January 2017) - Rohrschneider, Robert; Schmitt-Beck, Rüdiger
Abstract : Introducing the special issue, section (1) provides an overview of the election campaign, (2) discusses major aspects of the election's outcome and (3) highlights the broader theoretical implications of the contributions to the special issue to the research literature.